Mahatma Gandhi: A chronology - Publications Division; Compiled by Goswami, K. P. (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 1994)
Besides listing the main events in the personal and public life of Gandhiji, this chronology refers to his utterances commenting on the events or interpreting his actions. The references are given under respective dates and in direct or indirect form as found convenient.
Keywords: Mahatma Gandhi; Nation Maker